Direct medical costs of inpatient treatment for forearm fractures at Cu Chi Regional General Hospital in 2024 - Chau, Le Da Minh; Thao, Le Thi Quy; Bay, Vo Van; Trang, Phan Ngo Diem; Phuong, Nguyen Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Forearm fractures impose substantial financial burdens on patients and the healthcare system. Objectives: This study estimated the direct medical costs of forearm fracture treatment in the Department of Orthopedic Surgery at Cu Chi Regional General Hospital in 2024. Materials and methods: A retrospective cross-sectional study employing a total sampling technique reviewed medical records of inpatients with a primary diagnosis of forearm fracture (ICD-10 S52) at the Department of Orthopedics from January 2024 to December 2024. Direct medical costs and associated patient characteristics were analyzed. Results: A total of 407 inpatients were included in the study. Patients aged 18 - 65 years accounted for 75.40%. The overall direct medical cost amounted to 856,148,998 VND, of which 83.88% was reimbursed by Health Insurance. In cases of isolated trauma, the Total cost was 538,017,945 VND, whereas in polytrauma cases it reached 318,131,053 VND. Medical consumables constituted the largest cost component in the surgical cohort, whereas bed fees dominated the non-surgical cohort. Regression analysis identified age, length of stay, admission mode, injury type, and intervention type as significant factors influencing treatment costs (p < 0.05). Conclusion: This study highlighted significant variations in direct medical costs across different groups. Surgical interventions constituted the highest expenditures, mainly due to medical consumables and procedural fees. The Health Insurance Fund played a key role in reducing the financial burden borne by patients.